NO forms an adduct with serum albumin that has endothelium-derived relaxing factor-like properties. - Keaney, J F (1993)
Recent evidence suggests that sulfhydryl species can react with oxides of nitrogen under physiologic conditions and thereby stabilize endothelium-derived relaxing factor (EDRF) activity, but the presence of a specific in vivo thiol carrier for nitric oxide (NO) remains controversial. The single free sulfhydryl of serum albumin is the most abundant thiol species in plasma (approximately 0.5 mM) and is particularly reactive towards NO. To examine the potential role of serum albumin in endogenous nitric oxide metabolism, we synthesized S-nitroso-BSA (S-NO-BSA), a model S-nitroso-protein, and examined its effects on platelet function and coronary and systemic vascular tone in 16 mongrel dogs. Intravenous bolus S-NO-BSA markedly reduced mean arterial pressure in a dose-dependent manner and proved seven and a half-fold less potent than intravenous nitroglycerin and 10-fold less potent than intravenous S-nitroso-cysteine (half-maximal response of 75 nmol/kg compared to 10 and 7.5 nmol/kg, respectively; P < 0.05); when given by intravenous infusion (half-maximal response = 10 nmol/kg per min), however, S-NO-BSA and nitroglycerin were equipotent. Intravenous bolus S-NO-BSA had a greater duration of action than either nitroglycerin or S-nitroso-cysteine and produced marked prolongation of the template bleeding time associated with dose-dependent inhibition of ex vivo platelet aggregation (half-maximal response approximately 70 nmol/kg). Intracoronary S-NO-BSA increased coronary blood flow (mean +/- SEM) less effectively than nitroprusside, acetylcholine, or S-nitroso-cysteine (165% +/- 24% vs. 315% +/- 82%, 483% +/- 55%, or 475% +/- 66%, respectively; P < 0.05) although with much longer duration of action. On a molar basis, S-nitroso-cysteine proved more effective than S-nitroso-BSA, nitroprusside, or acetylcholine as an epicardial coronary vasodilator. Thus, serum albumin reacts with oxides of nitrogen to form a stable S-nitroso-thiol with properties reminiscent of authentic EDRF supporting the view that protein associated thiol may participate in the action and metabolism of EDRF.